Effectiveness of Moringa oleifera L. Extract and Royal Jelly in Addressing Toddler Malnutrition in Coastal Central Sulawesi - Basri, Hasan; Hadju, Veni; Reski, Rahayu Nurul; Hidayat, Ahmad Arif; Saharuddin, Muh Agung (Current Nutrition & Food Science, 2025)
IntroductionMoringa oleifera and honey are nutrient-rich local foods with the potential to combat malnutrition. Combining them may enhance their synergistic effects, offering a holistic nutritional solution.ObjectiveThis study assessed the impact of Moringa oleifera plus royal jelly (MRJ) capsules on the weight, height, and nutritional status of toddlers in high-stunting coastal areas of Tojo Una-Una District.MethodsA quasi-experimental design was used, with an intervention group receiving 500 mg of MRJ capsules daily for three months, and a control group with similar baseline characteristics. The study involved six high-stunting villages, with nutrition workers monitoring compliance. Height and weight were measured using standardized tools, while dietary intake was assessed via 24-hour recall. Data were analyzed using WHO Anthro 2006, NutriSurvey 2007, and JASP.ResultsBaseline characteristics and food intake were similar between groups. Post-intervention, significant differences were observed in weight (9.00 ± 1.29 kg vs. 8.45 ± 0.93 kg, p=0.042) and height (76.57 ± 3.43 cm vs. 74.23 ± 5.30 cm, p=0.041). The intervention group also showed greater improvements in weight gain (0.99 ± 1.3 kg vs. 0.26 ± 0.7 kg, p < 0.005) and height increase (5.01 ± 2.8 cm vs. 2.83 ± 4.2 cm, p = 0.019). Additionally, HAZ scores improved significantly in the intervention group (-1.96 ± 1.24 to -1.55 ± 0.96, p = 0.027).DiscussionThe findings align with previous research highlighting Moringa’s role in combating malnutrition. However, limitations include the non-RCT design, lack of a placebo group, and small sample size.ConclusionMRJ supplementation significantly improved weight, height, and HAZ in toddlers, suggesting its potential as a nutritional intervention in areas prone to stunting. Further randomized trials are recommended to validate these results.
Keywords: Moringa oleifera